Quality of life amongst post coronary artery bypass patients at the National Heart Institute, Malaysia - Ho SE; Noor Siah AA; Zaidah Z; Teoh KH; Gurbinder JS; Ismail MS; Choy YC; Mazeni A (Penerbit UKM, 2010)
Coronary Artery Bypass Grafting (CABG) surgery has increased the survival rate for individuals suffering from myocardial infarction or coronary ischemia. The present study aimed to examine the perception of quality of life amongst post CABG patients at the National Heart Institute Malaysia. A total of 69 post CABG patients, were studied using the Medical Outcomes Short Form 36 (SF-36). The findings showed that post CABG respondents possessed good level of quality of life (SF-36) physically and mentally. There were significant differences between the role physical in the physical functioning domains of quality of life with gender (t=0.286, p<0.05). Duration of physi-cal exercises of more than 20 minutes have positive effects on both physical (t=2.738, p<0.05) and mental components (t=7.326, p<0.05). The level of income influenced both the physical component (F=3.100, p<0.05), and mental component (F=4.272, p<0.05). Post CABG patients were found to have high quality of life post operatively. They were able to make comprehensive lifestyle changes through frequent physical exercises to accommodate their needs